Caracterización morfológica del cacao (Theobroma cacao L.) tipo Cv. CCN-51 en zonas de producción de los cantones Babahoyo, Montalvo y Ventanas de la Provincia de Los Ríos, Ecuador - Rojas Santillán, Jonathan Agustín (2020)
The investigation about “Morphological characterization of cocoa (Theobroma cacao L.) type Cv.CCN-51 in production areas of the Babahoyo, Montalvo and Ventanas cantons of the Los Ríos Province, Ecuador ¨, this was done in the cantones Montalvo for reason of the state of emergency by COVID 19 pandemic, originally three cantonese would be studied without clutch it was possible to characterize 330 trees distributed in 11 different farms of the canton, each with 30 trees. Proposed descriptors Cocoa Research Unit University of West Indians were used, adapted to the catalog of cocoa cultivars in Peru, Catalogue of cocoa clones, selected by CATIE for commercial plantings and the Colombia cocoa quality characteristics document; Catalogue of 26 Cultivars and the National Institute of Agricultural Research (INIAP). Fort he interpretation of date was used simple statistic and multivariate analysis As results it could be obtained that of the 11 farms characterized the existence of morphological descriptors of the plant that showed high homogeneity, coefficients of variation ranging from 0% to 16,31%, on the other hand, on the other hand, the morphological descriptor number of fruits per tree was the one with the highest coefficient of variation with a value of 42,10%, showing that the behavior for the variable was very heterogeneous.